Brand Singapore - KOH, Buck Song (Institutional Knowledge at Singapore Management University, 2021)
As the world gets a better grip on the Covid-19 pandemic, one outcome is becoming clear: Place branding— in particular, nation branding—is becoming more important than ever before.